MENTAL HEALTH CHALLENGES AND SOLUTIONS IN LOW AND MIDDLE INCOME COUNTRIES –A HEALTH SYSTEM PERSPECTIVE: Mental Health Challenges - Azad, Abrar Hussain; Mashhadi, Syed Fawad; Bibi, Iram (Pakistan Armed Forces Medical Journal, 2015)
There are many gaps in establishing an active mental health system in low and middle income countries. In this article we have reviewed multiple studies focusing low and middle income countries to explore the barriers, challenges, solutions and opportunities regarding improvement of mental health system in these countries. Literature emphasizes political with good financing ,effective policies ,multi-sartorial and holistic approach encompassing linkage between health and non-health sectors leading to equitable access of mental health to populations in low and middle income countries.